(untitled) - Davison, Gerald C. (New York, 1994)
This book introduce readers to abnormal psychology, addressing the causes of psychopathology as well as issues in the treatment and prevention of abnormal behavior. It uses four perspectives to study abnormal psychology: biological, psychoanalytic, learning, and cognitive.
Keywords: Psychology, pathological,Psychopathology,Bệnh học tâm lý